Research entitled: The effect of drugs on the economies of countries - Mohammed, Hamdi; Haddar, Khaled (The journal of contemporary issues in business and government, 2023)
Many studies have acknowledged the danger of drug abuse and its negative psychological and social effects on the individual and society, but many of them overlooked the economic effects that trouble specialists. This study aimed to shed light on the various effects of drugs on the economies of countries through their negative impact on increasing levels of Unemployment, public spending and the volume of money laundering operations, as well as pillows contribute to encouraging the smuggling of hard currency abroad and limit the value of savings and investment in the formation of the domestic product. However, what matters in this research is to stand on his proposals to reduce these effects and dangerous consequences of drugs, which are divided into three stages. In the first stage, countries try to prevent these illegal substances from entering their soil, and the second stage tries to limit the internal demand for them by sensitizing individuals. Its various damages, and the last stage concerns the treatment of punishment of those involved and the treatment of addicts.